Critical Analysis Of Documentary Productions In Malaysia - Abdullah, Mohd Mawardy (2015)
Audience acceptances of local documentary in Malaysia have lessened compared to those produced abroad which received an overwhelming response from local audiences. The documentary production industry in Malaysia seems increasingly miserable as a result of the cold reception from the audience. Therefore, this study focuses on assessing the current situation of local documentary production, identifying weaknesses of Malaysian produced documentary and make recommendations on how to improve the production of documentaries in Malaysia. Preliminary investigation, observations and interviews were conducted in the study in order to obtain useful data that affect the quality of a documentary. These data are then listed as factors that affect the quality of a documentary in the form of a conceptual diagram. A “Best Practices” was produced in the form of a Checklist as a guide for local documentary productions to produce a better documentary film.